Ovarian serous borderline tumors: specific characteristics of ultrasound images - M. A. Chekalova; I. Yu. Davydova; A. I. Karseladze; L. A. Mescheryakova; V. N. Kuznetsov; E. Yu. Cherkasov (Опухоли женской репродуктивной системы)
Ovarian serous borderline tumors are usually found in women of reproductive age and perimenopausal women. Therefore, the issue of preserving the reproductive and hormonal functions is highly relevant. We analyzed specific ultrasonic characteristics of ovarian serous borderline tumors by comparing preoperative ultrasound and postoperative morphological findings in 98 patients. Ultrasonography is an effective method of patient monitoring after conservative and ultraconservative surgeries for ovarian serous borderline tumors.